Känsla och mening i trädgården - Ekdahl, Marie; Kapusta, Gunnel (2006)
This thesis puts together general guidelines for the design of outdoor environment at nursing homes for people with dementia. The goal is to give the residents a greater quality of life with the garden.The garden must be safe and secure while offering places for fellowship or retirement and experiences of joy and competence. The plant material and other elements in the garden are inserted to stimulate the senses and to inspire to different activities.